Pengembangan Kecakapan Public Speaking melalui Media Podcast untuk Siswa Sekolah Menengah Atas - Satria Putri, Berlian Primadani (Charity : Jurnal Pengabdian Masyarakat, 2023)
Public Speaking Skills must be required by anyone who speaks whether in formal, non-formal, small or large forums. Not only a teacher must have good Public Speaking skills, but a student is also required to have good Public Speaking skills in conveying ideas or opinions. Along with the development of the era, someone who has the ability to speak publicly has capital in life, especially when added with foreign language skills, it will be easy to do human literacy. Podcast is a new media in the form of informal communication. This podcast criteria is very suitable for high school (SMA) children, especially the millennial generation in starting the world of public speaking. Podcasts can be a suitable media choice for high school students in practicing Public Speaking, especially as one of the implementations of Indonesian language subjects, especially those related to speech material.